Validating of Measurement Scale of Student Economics Behavior Using Exploratory and Confirmatory Factor Analysis - Januar Kustiandi; Sheerad Sahid; Iszan Hana Kaharudin (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
This research aims to develop and validate an instrument to measure students' economic behavior constructs. This research are contributes to studying students' habits in managing their daily consumption activities. Students at state universities studying economics education made up the research sample. Data analysis was conducted using two stages: exploratory factor analysis (EFA) for the 105 respondents in the pilot study and confirmatory factor analysis (CFA) for the 308 respondents in the field study. The study's findings demonstrate that the three-dimensional construct of economic behavior planning, buying or consuming, and saving consideration satisfies the criteria for validity and reliability, paving the way for additional investigation. After that, to identify additional variables that can regulate students' economic behavior, researchers might look at further elements that affect it.